A Heavy Heart: The Association between Weight and Emotional Words - Zhao, Xueru; He, Xianyou; Zhang, Wei (Frontiers in Psychology, 2016)
People often express emotion in language using weight (e.g., a heavy heart, light-hearted, light humor, or heavy-handed), but the question remains whether these expressions of emotion are rooted in the body. Six experiments used a priming paradigm to explore the metaphoric relation between weight perception and emotional words. Experiments 1 and 2 investigated the influence of weight perception on judgments of emotional words and the influence of emotional words on judgments of weight, respectively. A significant difference between the consistent condition (e.g., lightness corresponds to positive words and heaviness corresponds to negative words) and the inconsistent condition (e.g., lightness corresponds to negative words and heaviness corresponds to positive words) was found in Experiment 1 but not in Experiment 2. Experiments 3, 4, and 5 were conducted to exclude potential confounds. Experiment 6 was a repeated-measures study that was conducted to verify the weight-emotion effect. The study confirmed that weight perception affected judgments of emotional words. The results contribute to the growing literature on conceptual metaphor theory and embodied cognition theory.